Osteoblast Differentiation Is Enhanced in Rotary Cell Culture Simulated Microgravity Environments - Y. Joon Ko, DDS, MS;1,2 Rebecca S. Zaharias, BA;3 Denise A. Seabold, BA;3 (Journal of Prosthodontics, 2007)
As the aging population increases, more people will become reliant on regenerative dental medicine for implant therapy